The Implementation of Consumer Protection Act on Cosmetic Business Agents (Study of Cosmetic Supervision at Makassar Agency of Food and Drug Control) - Fitri Wulandari; Muh. Saleh Ridwan; Patimah Patimah (Jurnal Ilmiah Al-Syir'ah, 2019)
This study is entitled Implementation of the Consumer Protection Act on Cosmetic Business Agents (Study of Cosmetic Supervision at Makassar Agency of Food and Drug Control). This study describes how to supervise the implementation of consumer protection act on cosmetic businesses. To obtain answers to this problem, the writers use three methods of the data collection; Observations, interviews, and documentation. In field research, the writers use observation and interview instruments. Qualitative Data processing and the data analysis techniques that are used; Data reduction, the data presentation, and verification of data. The samples in this study were the Head of the Agency of Food and Drug Control, the Head of Examination Department, the Head of Enforcement Department, the Head of Testing Department, the Head of Information and Communication Department, some business agents and consumers. The results of this study indicated that the application of the consumer protection act has been carried out by cosmetic business agents in Makassar, the agents have applied all the rules relating to the production and distribution of products as well. Supervision of cosmetic businesses by Makassar Agency of Food and Drug Control both in the market and at the clinic has proceeded properly.